Commodification of Religious Sentiments and Threats to Diversity on Youtube Religious Content - Yasirul Amri; Ridho, Ali; Muhammad Anshori; Syailendra Reza Irwansyah; Muhamad Ali; Faridhotun Nisa (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
YouTube has become a lucrative platform for content creators, fostering the rise of popular Muslim scholars with distinct specialties and audiences. This phenomenon has been exploited by creators who commodify religious lectures by framing them as debates, contributing to the growing polarization among Indonesian Muslims. This study employs a qualitative approach, utilizing the framing analysis model of Zhongdang Pan and Gerald M. Kosicki to examine how religious sentiments are constructed and commodified on YouTube. It further explores audience interpretations to assess the impact of such framing. The findings reveal that content creators manipulate frames through strategically designed thumbnails and titles as key syntactic elements, while the sequencing of video clips reinforces framing at the script, thematic, and rhetorical levels. Audience engagement, as reflected in comments, largely demonstrates support for the content creators and the religious figures portrayed as victors in these debates. The study concludes that the commodification of religious sentiments through framing significantly intensifies polarization within the Indonesian Muslim community, posing a considerable threat to social and religious diversity.